Advances In Infection Control: Strategies For Preventing Healthcare-Associated Infections (The Review of Diabetic Studies, 2024)
Healthcare-associated infections (HAIs) pose a significant global challenge, with prevalence rates ranging from 3.6% to 12% in developed countries and 5.4% to 19.1% in lower-income settings. HAIs adversely impact patient safety, increase morbidity and mortality, and contribute to substantial healthcare costs. This review provides a comprehensive overview of contemporary advances in infection control strategies for HAI prevention. It examines the evolution of infection control principles, from Semmelweis's pioneering work on hand hygiene to the development of Standard and Transmission-Based Precautions. Key factors contributing to HAIs are discussed, including invasive devices, improper sterilization, antimicrobial misuse, staffing challenges, and patient comorbidities. Advances in infection surveillance and monitoring are highlighted, such as electronic surveillance systems, molecular and genomic methods, and artificial intelligence applications. Technological innovations in sterilization, environmental design, and personal protective equipment are explored. The review emphasizes the critical role of hand hygiene and behavioral interventions, discussing compliance monitoring, educational strategies, and leadership's influence on safety culture. Emerging challenges and risks are addressed, including multidrug-resistant pathogens, pandemic preparedness lessons from COVID-19, climate change impacts on microbial ecology, and global disparities in infection control. The review aims to inform healthcare professionals, policymakers, and researchers to strengthen infection prevention practices and improve patient outcomes worldwide.